TINGKAT PENGETAHUAN MAHASISWA KESEHATAN TENTANG DAGUSIBU OBAT DI UNIVERSITAS TADULAKO SULAWESI TENGAH - Amelia Rumi; Firdawati Amir Parumpu; Suci Wulandari (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2022)
DaGuSiBu (Get, Use, Save and Dispose) is one of the programs to increase public awareness regarding the proper and correct use and management of drugs through information on how to get, use, store and dispose of drugs properly. The purpose of this study was to determine the average percentage level of knowledge of Get, Use, Store and Dispose of Medicines and the level of knowledge of DaGuSiBu Medicine among health students at Tadulako University. This research method uses an observational research design with a cross sectional approach and data collection through a google form questionnaire on 354 health students class 2018-2020. The sampling technique used was purposive sampling. The results showed that the level of knowledge of health students at Tadulako University based on the average percentage in the aspect of Getting Drugs could be categorized enough with a percentage value of 61.81%, Use of Drugs was categorized as good with a percentage value of 80.11%, Save Medicines was categorized as less with a percentage value of 51, 81%, and wasting medicine was categorized as sufficient with a percentage value of 64.58%. The level of knowledge of Tadulako University's health students about DaGuSiBu Drugs that are included in the good category are (63.28%), the sufficient category is (32.20%) and the less category is (4.52%). The conclusion of this study, the knowledge of health students at Tadulako University about DaGuSiBu Medicine can be said to be good.   Keywords         : DAGUSIBU, Knowledge, Students Health